Bimbingan Teknis Pendirian Koperasi Bagi Calon Anggota Koperasi di Kabupaten Garut - Mulyana, Iwan (E-Coops-Day, 2024)
Community service through technical guidance for prospective cooperative members who wish to establish a cooperative is a very important program to provide knowledge and character formation for those who will later have to participate in the cooperative forum that will be formed. This technical guidance will be held on 21 and 22 October 2023 from 19.30 WIB to 11.30 WIB. The expected output, apart from the formation of solid and responsible management, supervisors and members, is the formation of a cooperative that carries out its services to members through the efforts required by cooperative members. Therefore, the presenters are experienced in theory and practice in cooperatives. The method provided in this Bimtek is by providing material in two directions and discussions related to cooperatives in practice and how to establish cooperatives. The topics given to prospective cooperative members will provide a deeper understanding of the implementation of the steps in establishing a cooperative from the initial stages to the formation of the cooperative.